Effects of the Home Ward Model on the Management of Distress Symptoms and the Quality of Care as Perceived by Caregivers of Terminally Ill Patients Who Died at Home - Thammachote, Pruksaporn; Chaliewsak, Issariya; Sae-chit, Kalaya (Princess of Naradhiwas University Journal, 2026)
Background and Objectives Some terminally ill patients prefer to spend their final days at home. The home ward model provides care that is comparable in quality to inpatient services. This study aimed to compare the effects of the home ward model on disturbing symptom management and caregiver-perceived quality of care before and after the intervention among terminally ill patients who died at home, including an assessment of caregiver satisfaction. Methods A quasi-experimental study with a single-group, pretest–posttest design was conducted in Mueang District, Songkhla Province, between December 2024 and April 2025. A purposive sample of 30 caregivers who met the inclusion criteria was recruited according to the Department of Medical Services’ home ward model. Data were collected using the Palliative Care Outcome Scale (POS) Carer-Questionnaire before and after receiving care on days 4 and 7, and continued until the patient’s death. Caregiver satisfaction was measured using the FAMCARE-2 Scale. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used to analyze general characteristics and satisfaction levels. Caregivers’ perceptions of care quality were compared using the Linear Mixed model and pairwise comparison tests. Results Following implementation of the home ward model, the mean outcomes of disturbing symptom management before and after receiving care on Days 4 and 7 were significantly different (p < 0.05). Overall, caregiver satisfaction was rated at the highest level. Conclusion and Recommendation The study revealed that the home-ward care model was found to reduce disturbing symptoms among terminally ill patients who died at home, which enhanced caregivers’ perception of the quality of care and resulted in the highest level of caregiver satisfaction. Therefore, the home ward care model should be extended to other patient groups to enhance quality of life and promote comprehensive, sustainable healthcare services in the future.